(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The present paper is the first to describe a complex of basic semiotic and cultural preconditions for the formation of a specific model of a synthetic linguistic personality, which can be considered both as an independent cognitive-pragmatic unit and as part of a discourse personality. In addition, the article addresses the qualitative features of the transformation of such key concepts as “culture,” “text,” and “discourse” in the context of the semiotic-cultural approach and specifies the concepts of “discourse personality” and “synthetic text.” The traditional study of literary text using a systemic linguistic approach does not allow one to fully appreciate the creative individuality of such text, and therefore there is a need to create an integrated metadisciplinary approach based on the achievements of peripheral disciplines. As a base of such an approach, linguistic culture study is recognized as an integrative humanitarian discipline. Based on a comprehensive analysis combining cognitive, descriptive, contextual, and comparative methods, the concept of synthetic linguistic personality has been clarified. It was determined that the rock poet’s cognitive-pragmatic program has a complex structure and includes four basic types of constructive/destructive cognitive-pragmatic directions: a) cognitive-pragmatic attitudes of spiritual self-identification; b) cognitive-pragmatic attitudes of ideology; c) cognitive-pragmatic attitudes of intention implementation; g) cognitive-pragmatic attitudes of intermediate result. Using the modeling method, the article presents a model of the synthetic linguistic personality of the rock poet K. Kinchev in the rock composition “Rock and Roll is Us.” On the example of the verbal component of this rock composition, the main mechanisms of interaction of cognitive-pragmatic programs of various representatives of Russian rock are revealed, and the qualitative features of the formation of a holistic meta-discourse cognitive-pragmatic program of Russian rock culture are identified.